Educação Infantil e currículo: conceitos e fazeres pedagógicos na Rede Municipal de Educação de São Paulo - Paulino, Regiane (2018)
This research aims to analyze the structure, organization and conceptions presented by the curricular documents for children's education, proposed by the Municipal Network of São Paulo, to start from this assessment, to verify if these characteristics contribute to the reproduction of pre-established pedagogical practices or open up possibilities for innovation, encouraging the exploration of new forms of pedagogical practices at this stage. For this, the chosen methodological approach contemplates the qualitative approach choosing the bibliographic research and documentary analysis that allows the researcher to maintain the focus on the object of study in a broader coverage of what could be directly researched besides to highlight the course of the pedagogical action in the chosen network as a context of research and its transformations through time. As a result, it was possible to perceive that the educational universe, especially with regard to Early Childhood Education, underwent great changes. The child gained prominence in the curriculum of the stage and the conceptions that underlie the practices were renumbered so that the space of the education of the child stopped being merely assistencialista to incorporate, much more than an educational position, an educative culture. The current curricular documents of the researched context, show great concern with the reflexive formation of professionals and the collective construction of the curriculum. In this new scenario, infants and children are considered protagonists of their learning and the teacher has the role of mediator and facilitator of this process where learning takes place through experiences, experiences and interactions privileging the playful. This study aims to contribute to the search for new paths in early childhood education, providing indications of how pedagogical practice can, in an innovative way, be delineated to incorporate emerging conceptions of the new curricular documents of the São Paulo Municipal Education Department